High Volume Low Density Culture of Milkfish (Chanos chanos Forsskal) in Floating Net Cages at North Bais Bay Manjuyod-side, Negros oriental - Manzano, Roger Ray S.; Uy, Peter L.; Ganancial Jr, Renato H. (JPAIR Multidisciplinary Research, 2010)
The study was conducted at Resources Production Technology (REPROTECH), Incorporated in north Bais Bay (Manjuyod side), Negros Oriental. The purpose of the study is to demonstrate the feasibility and viability of milkfish (Chanos chanos forsskal) cultured in 180-m3 (6m x 6m x 5m) High Volume Low Density (HVLD) floating net cages and established a benchmark for cage farmers using a technology that offers a promising strategy that can have enormous impact on both socio-economic growth and food security. Results showed that bangus attained an average body weight (ABW) of 376.32 grams, after an average day of culture (DOC) of 163. It also showed an excellent survival rate of 111% and a very satisfactory feed conversion ratio (FCR) of 2.4. The average production per unit cage reached 2,480 kg or 13.78 kg/m3 of cage volume. The project realized a profit margin of Php. 34.94 per kilogram, indicating that even if the market price per kilogram is reduced by 10% the project is still gaining. Milkfish production in HVLD floating cages is economically viable for small and medium enterprise (SMI) fish farmers and promises a very attractive Return of Investment (ROI) estimated at 64.18% and a payback period of 0.4 year.